2022
DOI: 10.1016/j.technovation.2021.102366
|View full text |Cite
|
Sign up to set email alerts
|

Human resource policies and firm innovation: The moderating effects of economic and institutional context

Abstract: This paper examines the effects of human resource (HR) policies on firm innovation. Specifically, we argue that firms who implement policies to stimulate job autonomy and performance-based pay will be more likely to innovate, as proxied by investments in R&D. In addition, we contend that the institutional (i.e., labour regulations) and competitive (i.e., pressure from imports) contexts in which a firm operates will affect the relationship between HR policies and innovation, albeit in different ways. We test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Moreover, there has been extensive research on mid-level influencing factors, such as the impact of financial analyst coverage ( Guo et al, 2019 ), market competition ( Yang M. J. et al, 2021 ), and other factors on firm innovation. At the micro level, researchers attempted to evaluate the impact of ownership structure ( Minetti et al, 2015 ), corporate policy ( Krammer, 2022 ), and CEO political preference ( Han, 2019 ) on corporate innovation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, there has been extensive research on mid-level influencing factors, such as the impact of financial analyst coverage ( Guo et al, 2019 ), market competition ( Yang M. J. et al, 2021 ), and other factors on firm innovation. At the micro level, researchers attempted to evaluate the impact of ownership structure ( Minetti et al, 2015 ), corporate policy ( Krammer, 2022 ), and CEO political preference ( Han, 2019 ) on corporate innovation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A concept that is closely related to job flexibility is job autonomy. In this regard, Laursen et al [41] and, more recently, Krammer [42] showed that employees' greater job autonomy contributes to the innovative performance of a firm (also see the literature review by Seeck and Diehl [43] on this relationship). Along similar lines, Arvanitis [25] found that greater decision-making power and span of control have positive impacts on both product and process innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas family firms with high attachment to tradition attribute great importance to the family's history and past (Kammerlander, Dessì, Bird, Floris, & Murru, 2015), family firms with low attachment to tradition are oriented to the future and consider their past something from which they need to evolve (Rondi et al, 2019). Although tradition and innovation have typically been portrayed as two antithetical concepts (Ingram et al, 2016), more recently, studies have questioned this view by identifying innovative family firms that are strongly attached to tradition (e.g., Rondi et al, 2019;2021;Suddaby & Jaskiewicz, 2020). While this research makes an important contribution to the study of family firm innovation, future work is needed to determine why family firms that vary in their attachment to tradition can achieve similar innovation outcomes (Erdogan et al, 2020;Rondi et al, 2019;2021).…”
Section: Innovation In Family Firmsmentioning
confidence: 99%